Postmodern worldview: the depiction of our time in Don DeLillo, Will Self and Salman Rushdie - Nishi, Zerin Ahmad (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in English, 2017.